FORMATION OF ICT COMPETENCES IN TEACHERS OF MATHEMATICS IN THE SYSTEM OF POSTGRADUATE EDUCATION (Pedagogy of Higher and Secondary Education, 2009)
In the article described the possibilities of forming the ICT competencies of teachers of mathematics in the process of training and self education using the new book" Innovative informatively - communicative technologies of teaching of mathematics", developed by authors .